Self-knowledge as an important factor in breast cancer diagnosis: a case study. - Guerra, Heloísa Silva (2020)
It is a case study whose objective was to report the difficulty in detecting a breast cancer, in which the diagnosis was guided by a single clinical finding. The period considering the information was from2016, but held in the first half of 2019 in the city of Goiás. There was underdiagnosis by various health professionals, after three mammograms and two ultrasound suggestive of benignity. Despite the results, the patient sought a referral hospital and tests repetition also showed benignity, but the adaptation of devices in the exam showed malignancy, to the point that the patient underwent chemotherapy, then mastectomy. Exercising self-knowledge is an important tool that contributes to female emancipation and expression of her empowerment, as well as the complete history, qualified listening and detailed physical examination are essential for accurate diagnosis; and timely treatment with a view to improving the quality of life of the patient.